Total and Partial Laser Arytenoidectomy for Bilateral Vocal Fold Paralysis. (17th October 2016) - Yılmaz, Taner; Altuntaş, Ozan Muzaffer; Süslü, Nilda; Atay, Gamze; Özer, Serdar; Kuşçu, Oğuz; Sözen, Tevfik
Abstract : Introduction . Treatment for bilateral vocal fold paralysis (BVFP) has evolved from external irreversible procedures to endolaryngeal laser surgery with greater focus on anatomic and functional preservation. Since the introduction of endolaryngeal laser arytenoidectomy, certain modifications have been described, such as partial resection procedures and mucosa sparing techniques as opposed to total arytenoidectomy. Discussion . The primary outcome measure in studies on BVFP treatment using total or partial arytenoidectomy is avoidance of tracheotomy or decannulation and reported success ranges between 90 and 100% in this regard. Phonation is invariably affected and arytenoidectomy worsens both aerodynamic and acoustic vocal properties. Recent reports indicate that partial and total arytenoidectomies have similar outcome in respect to phonation and swallowing. We use CO2 laser assisted partial arytenoidectomy with a posteromedially based mucosal flap for primary cases and reserve total arytenoidectomy for revision. Lateral suturing of preserved mucosa provides tension on the vocal fold leading to better voice and leaves no raw surgical field to unpredictable scarring or granulation. Conclusion . Arytenoidectomy as a permanent static procedure remains a traditional yet sound choice in the treatment of BVFP. Laser dissection provides a precise dissection in a narrow surgical field and the possibility to perform partial arytenoidectomy.